ANALISIS OLAH GERAK KAPAL DAN PENGARUH PENAMBAHAN FIN STABILIZER TERHADAP MOTION SICKNESS INCIDENCE PADA KAPAL FERRY 500 GT - Arya Adiwidyo Nugroho, (2023)
Ship movement due to sea waves that occur continuously will result in symptoms of illness such as headaches, vomiting and nausea which are generally called seasickness or motion sickness. For passenger ships, this is a requirement for passenger comfort and safety that must be considered at the ship design stage. In this study, the results of a motion response simulation were obtained on the Ro-Ro 500 GT ferry with the help of Maxsurf Motions Advance software so that the ship's response to passenger comfort can be seen by modifying the addition of anti-roll in the form of a fin stabilizer with the help of Maxsurf Modeler, Autodesk Inventor and Rhinoceros software. to improve seakeeping performance it was corrected with the NORDFORSK standard and also the Motion Sickness Incidence value was corrected with standard ISO 2631 criteria. Variations in the fin stabilizer used 3 models from Kongsberg namely NR22, Gemini 30 and Gemini 20. From the simulation results it is known that the model with the fin stabilizer is the Gemini 20 model has the most optimal Seakeeping and MSI values, there is a significant decrease in RMS Roll Motion and a decrease in OMSI values between the initial model and the Gemini 20 model variation with an average difference of 8%. Ships can move safely and comfortably in conditions of slight (sea-state 3) to moderate (sea-state 4) at wave heights of up to 1,6 m, it is predicted that less than 10% of passengers experience seasickness for 2 hours the ship sails on the heading bow quartering seas and head seas.